Application of Image Processing to Determine the Tomato Fruit’s Ripeness - Infana Ayu Ladipi; Amin Rejo; Endo Argo Kuncoro (Program Pascasarjana Universitas Sriwijaya, 2022)
This study aims to apply image processing techniques in determining the level of fruit maturity based on color and the relationship of color changes with physical and chemical properties in Servo F1 varieties of tomatoes. This research has been conducted at the Laboratory of Agricultural Product Chemistry, Department of Agricultural Technology, Faculty of Agriculture, Sriwijaya University, Indralaya. This research was conducted from February 2019 until July 2019. This study used a descriptive method. The measured parameters are color, texture, moisture content, total sugar, and total acid. The results showed that the use of image processing methods can help the process of fruit sorting by looking at the relationship between the percentage of red color with the age of picking, the physical and chemical properties of the fruit. The percentage of tomato fruit red color on average ranged from 5.99% for picking age 25+1 days AFB (After the Flowers Bloom), 36.3% for picking age 29+1 days AFB, 67.41% for picking age 32+1 days AFB, and 76.85% for picking age 35+1 days AFB. The coefficient of determination of the relationship between the percentage of red color with the age of picking, texture, water content, total sugar, and total acid was 0.959, 0.908, 0.902, 0.835, and 0.750, respectively.